Lay navigation across the cancer continuum for older cancer survivors: Equally beneficial for Black and White survivors?. Issue 5 (September 2019) - Pisu, Maria; Rocque, Gabrielle B.; Jackson, Bradford E.; Kenzik, Kelly M.; Sharma, Pradeep; Williams, Courtney P.; Kvale, Elizabeth A.; Taylor, Richard A.; Williams, Grant R.; Azuero, Andres; Li, Yufeng; Acemgil, Aras; et al.
Abstract: Objectives: The Patient Care Connect Program (PCCP), through lay navigators' distress assessments and assistance, was shown to lower healthcare utilization and costs in older cancer survivors. PCCP benefits and assistance needs for disadvantaged minorities (e.g., Black) vs. Whites are unknown. Materials and Methods: We examined the PCCP impact with retrospective analyses of Medicare claims (2012–2015) . Outcomes were quarterly costs and utilization (emergency room (ER), hospitalizations) for navigated and matched survivors. Repeated measures generalized linear models with normal (costs), and Poisson (utilization) distributions assessed differences in trends overall and separately for Blacks and Whites. With distress data for navigated survivors, we assessed high distress (score > 3), ≥1 distress cause (overall, by domain), and ≥ 1 assistance request by minority group. Results: Beneficiaries were: 772 Black and 5350 White navigated, and 770 Black and 5348 White matched survivors. Impact was: i) costs: -$557.5 Blacks ( p  < .001), −$813.4 Whites ( p  < .001); ii) ER: Incidence Rate Ratio (IRR) 0.97 Blacks (NS), 0.93 Whites ( p  < .001); iii) hospitalizations: IRR 0.97 Blacks (NS), 0.91 Whites ( p  < .001). There was no significant difference in impact across minority groups. No significant differences were found in high distress (29% Black, 25.1% White), ≥1 distress cause (61.6% Black, 57.8% White), or ≥ 1 assistance request (64.5% Black, 59.1% White). Blacks were more likely to have ≥1 distress cause in the Practical domain. Conclusion: The PCCP may benefit both Black and White older cancer survivors. Programs should consider the proportion of older survivors with high distress, and the specific needs of minorities.